Integrating Psychological, Pedagogical, and Managerial Theories in Coaching: A Systematic Literature Review - Nor Mita Ika Saputri; M. Syaifuddin (Universitas PGRI Yogyakarta, 2026)
This study aims to systematically examine and synthesize the theoretical foundations underlying contemporary coaching practices by integrating psychological, pedagogical, and managerial perspectives. Using a systematic literature review guided by the PRISMA framework, this study analyzed 44 national and international peer-reviewed journal articles published between 2020 and 2025. Data were selected through transparent inclusion and exclusion criteria and analyzed using thematic analysis to identify dominant theories and integrative patterns in coaching research. The findings reveal that psychological theories such as Self-Determination Theory, Psychological Safety, Positive Psychology, Cognitive-Behavioral approaches, and Transformative Learning emphasize intrinsic motivation, trust, and reflective change. Pedagogical frameworks, including Andragogy, Dialogic and Inclusive Pedagogy, and Technology-Enhanced Learning, highlight experiential, learner-centered, and culturally responsive coaching processes. From a managerial perspective, Systems Theory, Managerial Coaching, Organizational Change, Innovation Management, and Sustainable Leadership position coaching as a strategic mechanism for performance improvement and organizational sustainability. The synthesis proposes an Interdisciplinary Coaching Model grounded in evidence-based coaching, integrating motivation, learning, and organizational alignment. This study contributes theoretically by consolidating cross-disciplinary coaching frameworks and practically by offering a coherent foundation for designing adaptive, culturally sensitive, and sustainable coaching interventions. Keywords: change management, interdisciplinary coaching, PRISMA, positive psychology, systematic literature review